Robot motion characteristics for embodied interaction with humans using upper arm - Mitsuru JINDAI; Shunsuke OTA; Toshiyuki YASUDA; Tohru SASAKI (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2020)
Humans establish embodied interactions, such as bows and handshakes, when they first meet. Through these embodied interactions, it is believed that humans construct a relationship that is emotionally acceptable to each other. In interactions between humans and robots, the same efficiency is expected. There are two types of embodied interactions. The first type is interactions without physical contact, such as those in raising hand greetings and bows. The other type is interactions with physical contact, such as those in handshakes and hugs. Thus, differences are believed to exist between the motion characteristics of robots that are preferred by humans depending on the presence or absence of physical contact. Therefore, in this paper, the differences in motion characteristics of robots that are preferred by humans in their embodied interactions with robots depending on the presence or absence of physical contact are analyzed. First, in a raising hand greeting, which is an embodied interaction without physical contact, the motion characteristics are analyzed. Next, the motion characteristics preferred by humans are identified through sensory evaluations using a raising hand greeting robot system that is developed based on these analyses. Finally, the differences in the preferred motion characteristics with the presence or absence of physical contact are analyzed by comparing the preferred motion characteristics of a raising hand greeting with those of a handshake, which were clarified in a previous study.